This PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN GAME EDUKASI WORDWALL TERHADAP PENGUASAAN KOSAKATA BAHASA INGGRIS KELAS V SDN 1 HAURPANGGUNG - Mentary Sopiawati Pazri; Dea Asri Pujiasti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of using the educational game media Wordwall on the English vocabulary mastery of fifth-grade students at SDN 1 Haurpanggung. The research design used was a one group pre-test and post-test design. The sample consisted of 29 students of class V-A at SDN 1 Haurpanggung. Data were collected through a vocabulary mastery test administered before (pre-test) and after (post-test) the use of Wordwall. The results showed that the average pre-test score was 58.79, while the average post-test score increased to 81.55. The paired sample t-test analysis indicated a significance value of 0.000 < 0.05 and tcount 13.912 > ttable 2.048, which means there was a significant difference between the pre-test and post-test results. Therefore, it can be concluded that the use of the Wordwall educational game has a significant effect on improving students’ English vocabulary mastery.